Implikasi Cerai Mati bagi Kedudukan Istri terhadap Hutang Perbankan Peninggalan Suami Menurut Perspektif Hukum Perdata dan Hukum Islam - Mohamad Yuflih Huda Maheswara (Jurnal Hukum Lex Generalis, 2022)
Marriage is a legal agreement between a man and a woman to form a family and continue their offspring. Marriages can end, one of which is due to the death of the husband by leaving property and debts. Among the various debts, one of the most common cases is banking debt. On the other hand, the knowledge of the wife's position on the inheritance of the late husband's debt is widely encountered. The wife is in a vulnerable position for violation of obligations. The wife's obligation to pay off is set forth by reviewing how Islamic law and civil law regulate debt issues by juridical-normative methods.